Tradition as a communication system. A pragmatic approach - Grad, Paweł (Hybris, 2015)
A context of my paper is the debate on reason, tradition and traditional communities, in which this moral and epistemological issues were discussed as a part of general socio-philosophical theory of modernity. In particular I intend to locate my considerations in the context of formal-pragmatic theory of modern communicative rationality developed by Jürgen Habermas and Robert Brandom. I will provide a competitive model of the rationality of tradition by applying a conceptual toolkit of pragmatically oriented analysis to explain practices connected with vocabulary of tradition. I argue that tradition as a communication system has a fully rational structure. My main claim is that communicative structure of tradition has a rational structure of language game. This structure includes defined principles of communication for members of closed tradition-grounded community and rule of inclusion for potential new members. Firstly I consider closely internal principles of communication within the framework of tradition contrasting them shortly with normative-deontic rules of the postenlightenment idea of pragmatic communication discussed by Jürgen Habermas and Robert Brandom. After that I examine the rule of inclusion — the rule, which mediates between closed system of tradition-based community and his environment.